Implementation of Health Policy on the Effectiveness of the Poor Certificate Program - Desy Miranti (Program Pascasarjana Universitas Negeri Makassar, 2022)
This study focuses on the implementation of health policies on the effectiveness of the Poor Certificate Program (Indonesia: Program Surat Keterangan Miskin / SKM) in Cangkuang District, Bandung Regency which is not yet optimal. This can be seen from the lack of communication and socialization of employees to the community, inadequate human resources that hinder the implementation of the program, the bureaucratic structure which is usually long, so that people who do not understand to participate in this program experience many things, obstacles. The purpose of this study is to develop knowledge in the field of public administration, especially regarding the effectiveness of the implementation of the SKM in Cangkuang District, Bandung Regency. The writer chose the descriptive qualitative research method because the author wanted to describe in detail and interpret the data or symptoms obtained during the research. Data collection techniques in this study using observation, interviews, literature studies and other data sources that support the research. The results showed that the effectiveness of the implementation of the SKM in Cangkuang District, Bandung Regency was quite effective even though there were several obstacles, this was due to factors that were not yet optimal on effectiveness, both in terms of adaptability, the ability of officers to carry out their work, and resource achievement.